2021
DOI: 10.1371/journal.pone.0252113
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of potato solid waste into antifungals and biopigments using Streptomyces spp.

Abstract: Potato waste was processed and used as a sole substrate for simultaneously producing antifungals and biopigments using Streptomyces spp. Out of three different Streptomyces isolates, strain SO6 stood out due to its ability to produce antifungals against economically important fungal phytopathogens and intracellular biopigments using potato waste powders without additional nutrients. This strain also showed the potential to secrete a broad range of enzymes for fermentation of eight sugars that could be involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…has recently opened a door for the valorization of microbial‐generated products from food waste. For example in a recent, study by Schalchli et al ( 2021 ) Streptomyces spp. were used to produce antifungals and biopigments from potato solid waste.…”
Section: Applications Of Streptomyces Spp In Texti...mentioning
confidence: 99%
“…has recently opened a door for the valorization of microbial‐generated products from food waste. For example in a recent, study by Schalchli et al ( 2021 ) Streptomyces spp. were used to produce antifungals and biopigments from potato solid waste.…”
Section: Applications Of Streptomyces Spp In Texti...mentioning
confidence: 99%
“…The capacity of strain SO6 to produce intracellular biopigments and antifungals against commercially important fungal phytopathogens using powdered potato waste without the addition of additional nutrients made it stand out among the three different Streptomyces isolates. This strain also shows the capacity to release several enzymes for the fermentation of eight sugars that may be involved in the bioconversion of potato trash (Schalchli et al, 2021 ). The only substrate for the concurrent generation of antifungals and biopigments was prepared and supplied to Streptomyces spp.…”
Section: Biotechnological Industry Potato Waste Management and Utiliz...mentioning
confidence: 99%
“…Out of three separate Streptomyces isolates, strain SO6 stood out due to its capacity to produce intracellular biopigments and antifungals against commercially important fungal phytopathogens using powdered potato waste without the addition of additional nutrients. Also, this strain showed the capacity to release a range of enzymes for the fermentation of eight sugars that may be involved in the bioconversion of potato waste (Schalchli et al, 2021 ). Making pigment from M. purpureus Went NRRL 1992 using potato waste powder has some advantages.…”
Section: Biotechnological Industry Potato Waste Management and Utiliz...mentioning
confidence: 99%
“…The use of glycerol, a by-product of biodiesel manufacture as a carbon source by R. glutinis TISTR 5159 led to concomitant production of lipids (6.05 g/L) as well as carotenoids (135.25 mg/L) in a stirred tank bioreactor ( Saenge et al, 2011 ). Among the pioneer reports on biopigment production by Streptomyces genus utilizing agro-industrial wastes, Schalchli et al (2021) reported 1.75 mg/g pigment production by Streptomyces sp. strain SO6 utilizing potato waste as the sole nutrient source.…”
Section: Agro-industrial Wastes As Low-cost Substrates For Pigment Pr...mentioning
confidence: 99%